Determining Role of Temperature Chart while Evaluating Specific Expenses of Organic Fuel - A. P. Nesenchouk; T. V. Ryzhova; S. S. Kovalev; V. I. Tchernyshevitch; V. V. Shidlovsky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers designing principles of operational space continuous heating and heat-treating furnaces at mechanical engineering, automotive and tractor enterprises in theRepublicofBelarus. A role of temperature chart on heating metallic charge while evaluating specific expenses of organic fuel in heating and heat-treating furnaces of mechanical engineering, automotive and tractor industries.